Pengembangan Sistem Administrasi Pengolahan Data KKN Universitas Diponegoro - Mastam Aji; Kodrat Iman Satoto; Rinta Kridalukmana (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2015)
KKN Program is the activity which is done by student. The activities shall be conducted as part of the student learning activities. In practice, there is a problem in the management of KKN’s data, such as period data, district data, sub-district data, village data, Supervisor’s data (DPL), zoning data, area history data, KKN participant data, preparation of a valuation and not centralized data. One of them is KKN Program which is conducted by Diponegoro University. KKN Program will require an application to manage data in order to improve work efficiency and the smoothness of KKN Program. The application of KKN Data Processing Administration is a web-based application, created by use the PHP programming language within the scope of the Code Igniter Framework and MySQL database. The development method is done by use the waterfall method, whereas in the application design is using UML modeling. The results of this application design is the creation of a web-based application that can manage KKN data in the Diponegoro University, such as period data processing, district data, data sub-district, village data, Supervisor’s data (DPL), zoning data, KKN participant data, list of participants, and the value of area history data that has been used in previous KKN program.